Is Traditional Management Accounting Still in Use? Contemporary Issues - Alsharari, Nizar Mohammad; Lasyoud, Alhashmi Aboubaker (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
This paper aims to review the relevant literature on the role of management accounting in organizational management. It also compares traditional and new or strategic management accounting and their limitations. It focused on the role of management accounting in the constitution of organizations and the ways in which management accounting systems as structures of intentionality both shape and are shaped by shared norms and understandings. The findings help to understand the concerns of the current mainstream in management accounting literature. In fact, the findings cohere with Hopwood and Scapens and their followers in the sense that management accounting is not a static phenomenon but one that changes over time to reflect new forms and practices. It was also found that management accounting is part and parcel of organizational change. By reviewing a subset of the studies on accounting history published during the period 1980 - 2018, this paper updates accounting history literature by focusing on management accounting research. The paper also contributes to the existing literature by presenting the discussions of management accounting and organizational change. However, other studies can consider this paper as starting point to examine other areas of accounting such as financial accounting.